A zirconia-based ceramic material with high phase stability and resistance to CMAS corrosion, and preparation method and application thereof
By using binary rare earth oxide co-doping method in zirconia-based ceramic materials, the problems of phase transformation and CMAS corrosion of YSZ thermal barrier coating at high temperatures are solved, and the effects of high phase stability and resistance to CMAS corrosion are achieved. .
Patent Information
- Application Number
- CN202310710695.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-15
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-06-15
AI Technical Summary
The existing YSZ thermal barrier coatings have phase transition problems at high temperatures, resulting in increased stress in the ceramic layer and failure of the coating, and are susceptible to CMAS corrosion in complex environments.
The stable zirconia material is co-doped with binary rare earth oxides (scandium oxide and dysprosium oxide). By controlling the doping amount and molar ratio, a zirconia-based ceramic material with high phase stability and resistance to CMAS corrosion is formed.
It has phase stability at 1300-1600°C, which significantly improves the high-temperature CMAS corrosion resistance of ceramic materials and extends the thermal cycle life of the coating.
Smart Images

Figure CN116891383B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic materials, and in particular relates to a zirconia-based ceramic material with high phase stability and resistance to CMAS corrosion, and a preparation method and application thereof. Background Art
[0002] Thermal barrier coating is a key technology for high-temperature thermal protection of hot end components of aircraft engines. It can effectively shield the thermal shock and chemical erosion of high-temperature combustion gases on the surface of high-temperature alloys of hot end components, thereby improving the working efficiency of aircraft engines and extending their service life. 6-8wt.% Y2O3 partially stabilized ZrO2 (YSZ) has low thermal conductivity, a thermal expansion coefficient matching that of the substrate, and excellent mechanical properties. It is currently a widely used thermal barrier coating surface ceramic layer material in the field of aircraft engines. However, for more demanding application environments (1200-1600℃, less cooling airflow), the YSZ coating will undergo a transformation from a non-equilibrium tetragonal phase (t′) to an equilibrium tetragonal phase (t) and a cubic phase (c), and then the tetragonal phase will transform to a monoclinic phase (m). During this phase change, the volume expands by about 3.5vol.%. The volume change increases the stress in the ceramic layer, which eventually leads to coating failure. In addition, YSZ is very easy to sinter at high temperature. During the sintering process, the pores and cracks disappear, resulting in an increase in the Young's modulus of the coating. These changes will increase the elastic energy stored in the coating, thereby reducing the thermal cycle life of the coating. In addition, when the thermal barrier coating is in service for a long time under complex environments such as high temperature, high pressure, high-speed particle impact and molten salt corrosion, CMAS corrosion is one of the important factors leading to its failure. CMAS (CaO-MgO-Al2O3-SiO2) mainly comes from environmental sediments carried by the airflow, such as dust, sand, ash or other siliceous materials, and impurities in the fuel. In the service environment, these impurities adhere to the surface of the thermal barrier coating, melt into a glassy melt as the working temperature increases, penetrate into the ceramic material through the gaps and cracks on the surface of the coating, react with the coating, accelerate the phase change and sintering of the coating, and finally cause the coating to fail. Therefore, it is of great significance to study and develop new thermal barrier coating materials that have phase stability and resistance to CMAS corrosion under higher temperature conditions. Summary of the invention
[0003] In view of this, the object of the present invention is to provide a zirconia-based ceramic material with high phase stability and resistance to CMAS corrosion, and a preparation method and application thereof. The zirconia-based ceramic material provided by the present invention has phase stability at 1300-1600°C and has excellent resistance to CMAS corrosion at high temperatures.
[0004] The invention provides a zirconia-based ceramic material with high phase stability and resistance to CMAS corrosion. The zirconia-based ceramic material is a binary rare earth oxide co-doped stable zirconia material. The binary rare earth oxide comprises dysprosium oxide and scandium oxide.
[0005] In the embodiments of the present invention, CMAS corrosion refers to environmental deposits carried by the airflow, such as dust, sand, ash or other siliceous materials, and impurities in the fuel, the main components of which are CaO-MgO-Al2O3-SiO2; in the service environment, these impurities (CMAS) adhere to the surface of the thermal barrier coating, and as the working temperature increases, they melt into a glassy melt, penetrate into the interior of the ceramic material through the gaps and cracks on the surface of the coating, react with the coating, accelerate the phase change and sintering of the coating, and ultimately cause the coating to fail.
[0006] In an embodiment of the present invention, the binary rare earth oxide co-doped stabilized zirconia (system) material is a rare earth oxide stabilized zirconia material conventionally understood in the art, such as yttria stabilized zirconia, etc. In an embodiment of the present invention, the doping amount or content of the binary rare earth oxide in the (high phase stability, CMAS corrosion resistant) zirconia-based ceramic material can be 4-8 mol%, or 5 mol%, 6 mol%, 7 mol%. In an embodiment of the present invention, the molar ratio of scandium oxide to dysprosium oxide can be 1: (6-1), or 1: 5, 1: 4, 1: 3, 1: 2, 1: 1. In an embodiment of the present invention, the composition of the zirconia-based ceramic material with high phase stability and CMAS corrosion resistance may include Sc2O3, Dy2O3 and ZrO2.
[0007] The present invention provides a method for preparing a zirconia-based ceramic material with high phase stability and resistance to CMAS corrosion as described in the above technical solution, comprising:
[0008] The composite ceramic powder is pressed and sintered to obtain a zirconia-based ceramic material with high phase stability and resistance to CMAS corrosion;
[0009] The composite ceramic powder comprises: Sc2O3, Dy2O3 and ZrO2.
[0010] In an embodiment of the present invention, the total molar amount of scandium oxide and dysprosium oxide in the composite ceramic powder can be 4-8 mol.% of the composite ceramic powder (total molar amount of Sc2O3, Dy2O3 and ZrO2), or it can be 5 mol%, 6 mol%, or 7 mol%; the molar ratio of scandium oxide and dysprosium oxide can be 1:(6-1), or it can be 1:5, 1:4, 1:3, or 1:2.
[0011] In an embodiment of the present invention, the method for preparing the composite ceramic powder may include:
[0012] The hydroxide precursor is dried and calcined to obtain composite ceramic powder.
[0013] In an embodiment of the present invention, the preparation method of the hydroxide precursor may include:
[0014] The mixed cation solution is subjected to a coprecipitation reaction in a reaction mother solution to obtain a hydroxide precursor;
[0015] The mixed cationic solution comprises: solution A and solution B;
[0016] The solute in the solution A includes scandium oxide and dysprosium oxide; the solvent in the solution A includes hydrochloric acid;
[0017] The solution B is selected from zirconium oxychloride solution;
[0018] The reaction mother liquor is selected from water, and the pH value of the reaction mother liquor is adjusted by using ammonia water. The pH value of the reaction mother liquor is 9-13.
[0019] In an embodiment of the present invention, the method for preparing solution A may include:
[0020] Scandium oxide and dysprosium oxide are dissolved in hot hydrochloric acid to obtain a clear solution, which is solution A.
[0021] In an embodiment of the present invention, the temperature of the hot hydrochloric acid can be selected from 80°C to 150°C, such as 90°C, 100°C, 110°C, 120°C, 130°C, 140°C; the volume ratio of the hot hydrochloric acid to scandium oxide can be selected from (6-4):1, such as 5:1; the volume ratio of the hot hydrochloric acid to dysprosium oxide can be selected from (4-2):1, such as 3:1. In an embodiment of the present invention, the molar ratio of scandium oxide to dysprosium oxide is consistent with that of the above technical solution, which will not be repeated here.
[0022] In an embodiment of the present invention, the solvent in the zirconium oxychloride solution may be water, such as deionized water; the molar concentration of the zirconium oxychloride solution may be selected from 0.5 to 2.0 mol / L, such as 1.0 mol / L, 1.5 mol / L.
[0023] In an embodiment of the present invention, the mixed cation solution may include Zr 4+ Sc 3+ and Dy 3+ In an embodiment of the present invention, the method for preparing the mixed cation solution may include:
[0024] Solution A and solvent B are mixed to obtain a mixed cationic solution.
[0025] In an embodiment of the present invention, the usage ratio of solution A and solution B can be set according to the ratio of dysprosium oxide and scandium oxide in the composite ceramic powder described in the above technical solution, so that the ratio of each component in the obtained composite ceramic powder meets the above requirements.
[0026] In an embodiment of the present invention, in order to inhibit particle agglomeration, a dispersant may be added to the mixed cationic solution; the dispersant may be an alcohol dispersant, such as polyethylene glycol (PEG2000) or ethanol (anhydrous ethanol); the amount of the dispersant may be 1 to 5% of the mass of the pre-obtained hydroxide precursor, such as 2%, 3%, or 4%.
[0027] In an embodiment of the present invention, the reaction mother liquor can be deionized water, and the pH value of the reaction mother liquor can be adjusted by using an ammonia solution as a co-precipitant; the volume ratio of ammonia water to water in the ammonia solution can be (0.8-1.2):1, or 1:1; the pH value of the reaction mother liquor can be 9-13, such as 10, 11, or 12.
[0028] In an embodiment of the present invention, during the coprecipitation reaction, the mixed cationic solution can be slowly dripped into the reaction mother liquor to carry out the coprecipitation reaction; magnetic stirring can be carried out during the coprecipitation reaction, and stirring is continued for 20 to 40 minutes, such as 30 minutes, after the titration is completed; during the coprecipitation reaction, ammonia water can be used as a precipitant to adjust the pH value of the reaction system to remain unchanged, and the pH value during the coprecipitation reaction can be kept unchanged by adjusting the titration rate of the cationic solution and the precipitant. The pH value during the coprecipitation reaction can be maintained at 9 to 13, such as 10, 11, and 12.
[0029] In the embodiment of the present invention, after the coprecipitation reaction is completed, the reaction mixture may be allowed to stand to ensure that all metal cations are completely precipitated; the standing time may be 12 to 36 hours, such as 18 hours, 24 hours, or 30 hours.
[0030] In the embodiment of the present invention, after standing, the obtained coprecipitate can be filtered, washed, and dried to obtain hydroxide precursor powder.
[0031] In the embodiment of the present invention, water can be used for washing in the washing process, and then Cl in the filtrate after washing can be detected. - ; then wash with ethanol to inhibit powder particle agglomeration.
[0032] In the embodiment of the present invention, the washing water can be deionized water; AgNO3 solution can be used to detect whether the filtrate contains Cl - , wash with water until free of Cl - The molar concentration of the AgNO3 solution may be 0.5-1.5 mol / L, or 1 mol / L. In the embodiment of the present invention, the ethanol used for washing may be anhydrous ethanol, and the number of ethanol washings may be 2-4 times, such as 3 times.
[0033] In an embodiment of the present invention, the filter cake obtained after washing is dried, and the drying method can adopt a two-step method, which may include:
[0034] First, the precipitate is dried at a first temperature for a first time to remove ethanol from the precipitate; and then the precipitate is dried at a second temperature for a second time to fully remove water from the precipitate.
[0035] In an embodiment of the present invention, the first temperature can be selected from 80 to 90°C, such as 85°C; the first time can be selected from 10 to 20h, such as 15h; the second temperature can be selected from 110 to 150°C, such as 120°C, 130°C, 140°C; the second time can be selected from 10 to 20h, such as 15h.
[0036] In an embodiment of the present invention, the hydroxide precursor may be ball-milled before being dried; the ball-milling time may be 2 to 4 hours, such as 3 hours; the ball-milling may be performed using a ball mill, and the rotation speed of the ball mill may be 200 to 400 r / min, such as 300 r / min; the ball-milling medium may be ethanol, such as anhydrous ethanol.
[0037] In an embodiment of the present invention, the drying temperature of the hydroxide precursor after ball milling can be selected from 80°C to 120°C, such as 90°C, 100°C, and 110°C; the drying time can be selected from 8h to 12h, such as 9h, 10h, and 11h.
[0038] In an embodiment of the present invention, the calcination temperature of the hydroxide precursor can be selected from 500-900°C, such as 600°C, 700°C, 800°C; the calcination time can be selected from 2-10h, such as 3h, 4h, 5h, 6h, 7h, 8h, 9h.
[0039] In an embodiment of the present invention, the composite ceramic powder may be sieved before being pressed; the mesh size of the sieve may be 100-400 meshes, such as 200 meshes or 300 meshes.
[0040] In an embodiment of the present invention, the composite ceramic powder is sieved and then pressed into a green compact. The pressing pressure of the green compact can be selected from 10 to 30 MPa, such as 20 MPa; the holding time can be selected from 1 to 2 min; a cylindrical green compact can be obtained after pressing, and the diameter of the cylindrical green compact can be 8 to 12 mm, such as 10 mm; the length can be 1 to 2 mm, such as 1.5 mm. In an embodiment of the present invention, the green compact obtained after pressing can also include: degumming it; the temperature of the degumming treatment can be selected from 450 to 550 ° C, such as 480 ° C, 500 ° C, 520 ° C; the time of the degumming treatment can be selected from 0.8 to 1.2 hours, such as 1 hour.
[0041] In an embodiment of the present invention, the debonded pressed green sheet is subjected to high-temperature sintering to obtain a densified ceramic material. The high-temperature sintering temperature can be selected from 1400 to 1600°C, such as 1400°C, 1500°C; the sintering time can be selected from 6 to 12h, such as 7h, 8h, 9h, 10h, 11h.
[0042] In an embodiment of the present invention, the densified ceramic material can be subjected to a high-temperature phase stability test, the high-temperature phase stability test temperature is selected from 1300 to 1600° C., the insulation time is selected from 100 to 300 hours, and the monoclinic phase content is tested to evaluate its phase stability.
[0043] The present invention provides a thermal barrier coating, comprising:
[0044] The above technical solution provides a zirconia-based ceramic material with high phase stability and resistance to CMAS corrosion.
[0045] In an embodiment of the present invention, a zirconia-based ceramic material with high phase stability and resistance to CMAS corrosion can be applied to a thermal barrier coating or an environmental barrier coating, and prepared into a coating as the surface layer of a thermal barrier coating or the surface layer of an environmental barrier coating; the thermal barrier coating can be a thermal barrier coating for high-temperature thermal protection of the hot end components of an aircraft engine.
[0046] The present invention provides a zirconia-based ceramic material with high phase stability and resistance to CMAS corrosion, and a preparation method and application thereof. The zirconia-based ceramic material of the present invention can be used as a thermal barrier coating material to prepare a thermal barrier coating, and has phase stability at 1300-1600°C. Moreover, the material provided by the present invention has excellent resistance to CMAS corrosion at high temperatures and can protect a high-temperature alloy substrate from CMAS molten salt corrosion.
[0047] The present invention provides a zirconia-based ceramic material with high phase stability and resistance to CMAS corrosion. The zirconia is stabilized by scandium oxide and dysprosium oxide composite doping, and a metastable tetragonal crystal structure without phase change at room temperature to 1600°C can be obtained. By controlling the addition amount of Sc2O3 and Dy2O3 and the ratio of the two stabilizers, the dissolution-precipitation mineralization process of the zirconia-based ceramic and CMAS can be slowed down, so that the CMAS corrosive agent forms a relatively dense glassy substance on the ceramic surface, which hinders the corrosion of the CMAS molten salt into the ceramic interior, thereby making the ceramic-based material have excellent resistance to CMAS corrosion. Compared with single dysprosium oxide stabilized zirconia, the dysprosium oxide and scandium oxide synergistically stabilized zirconia ceramics in the present invention have significantly improved phase stability and CMAS corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 The X-ray diffraction pattern of the 1Sc3.5DySZ composite ceramic powder prepared in Example 1 of the present invention;
[0049] Figure 2 This is a microscopic morphology of the 1Sc3.5DySZ ceramic body prepared in Example 1 of the present invention after being etched by CMAS;
[0050] Figure 3 The X-ray diffraction pattern of the 2Sc3.5DySZ composite ceramic powder prepared in Example 2 of the present invention;
[0051] Figure 4 The X-ray diffraction pattern of the 3Sc3.5DySZ composite ceramic powder prepared in Example 3 of the present invention;
[0052] Figure 5 The X-ray diffraction pattern of the 3Sc3.5DySZ ceramic body prepared in Example 3 of the present invention after heat treatment at 1400°C for 110h;
[0053] Figure 6 The X-ray diffraction pattern of the 4Sc3.5DySZ composite ceramic powder prepared in Example 4 of the present invention;
[0054] Figure 7 The X-ray diffraction pattern of the 4Sc3.5DySZ ceramic body prepared in Example 4 of the present invention after heat treatment at 1400°C for 110h;
[0055] Figure 8 This is a microscopic morphology of the 4Sc3.5DySZ ceramic body prepared in Example 4 of the present invention after being etched by CMAS;
[0056] Fig. 9 The X-ray diffraction pattern of the Dy2O3-ZrO2 ceramic powder prepared in Comparative Example 1;
[0057] Fig.10 The X-ray diffraction pattern of the Dy2O3-ZrO2 ceramic powder prepared in Comparative Example 1 after heat treatment at 1400°C for 110h;
[0058] Fig.11 This is the microscopic morphology of the Dy2O3-ZrO2 ceramic body prepared in Comparative Example 1 after CMAS corrosion. DETAILED DESCRIPTION
[0059] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0060] Example 1 Preparation of 10 g 1 mol.% Sc2O3-3.5 mol.% Dy2O3-ZrO2
[0061] 0.10439 g of scandium oxide and 0.98820 g of dysprosium oxide were respectively dissolved in hot hydrochloric acid, 23.29502 g of ZrOCl2·8H2O was dissolved in deionized water, 0.5 g of polyethylene glycol (PEG2000) was dissolved in 10 ml of anhydrous ethanol as a dispersant, the above solutions were mixed and fixed to a solution concentration of 0.5 mol / L to obtain a mixed salt solution.
[0062] Ammonia water and water in a volume ratio of 1:1 were measured as a precipitant; 100 ml of deionized water was taken as a reaction mother solution, the pH value of the reaction mother solution was adjusted to 10 with a precipitant, and the mixed salt solution and the precipitant were simultaneously dripped into the reaction mother solution for a co-precipitation reaction. Magnetic stirring was applied during the precipitation process, and the titration rate of the mixed salt solution and the precipitant was adjusted to ensure that the pH value of the entire reaction process was constant at 10. After the titration was completed, stirring was continued for 30 minutes, and the precipitate was allowed to stand for 24 hours. The precipitate was repeatedly washed several times with deionized water by centrifugal washing until less than Cl was detected by a 1 mol / L AgNO3 solution. - The precipitate was then washed with anhydrous ethanol for three times, and the filter cake obtained after filtering the precipitate was dried at 85°C for 6 hours, and then dried at 110°C for 12 hours to obtain a hydroxide precursor powder.
[0063] The precursor powder was placed in a ball mill and milled for 2 hours at a ball milling rate of 200 r / min. The ball milling medium was anhydrous ethanol. The milled slurry was dried and the obtained dry precursor powder was calcined at 800°C for 2 hours to obtain a 1 mol.% Sc2O3-3.5 mol.% Dy2O3-ZrO2 (1Sc3.5DySZ) composite ceramic powder. The phase composition of the composite powder is as follows: Figure 1 The X-ray diffraction pattern shown shows a single tetragonal phase structure.
[0064] The 1Sc3.5DySZ ceramic powder was passed through a 200-mesh sieve and then pressed at a pressure of 12 MPa and a holding time of 1 min to obtain a particle size of The ceramic compact was subjected to debonding heat treatment at 500°C for 1 h, and then the debonded sample was sintered at 1400°C for 10 h in a box furnace to densify it and obtain a 1Sc3.5DySZ ceramic body.
[0065] The ceramic body prepared in Example 1 was heat treated at 1400°C for 110 h, and the phase composition was analyzed by X-ray diffraction. Its high-temperature phase stability was evaluated by the monoclinic phase content. The test results showed that no diffraction peak of the monoclinic phase was found, and the 1Sc3.5DySZ ceramic body still maintained a single tetragonal phase structure. After the 3.5DySZ powder prepared in Comparative Example 1 was heat treated at 1400°C for 110 h, the tetragonal phase was completely transformed into cubic phase c and monoclinic phase m, indicating that the phase stability of 1Sc3.5DySZ ceramic is significantly improved compared with that of 3.5DySZ.
[0066] The oxide powder of 29.73wt% CaO-6.27wt% MgO-21.66wt% Al2O3-42.34wt% SiO2 was ball-milled in a high-purity zirconium oxide ball mill at a ball-milling rate of 200r / min for 6h, and the slurry obtained after ball milling was placed in an oven and dried at 85℃ for 10h. The dried powder was heat-treated at 1300℃ for 10h to fully react and phase-change to obtain a glassy composite oxide, which was sieved through a 200-mesh sieve to obtain the desired CMAS powder. 0.2g CMAS powder was mixed with 5mL anhydrous ethanol to obtain a suspension, and the suspension was coated on the surface of the sintered body with a coating amount of 10mg / cm 2 The ceramic sheet coated with CMAS was heat treated at 1300℃ for 70h, and the microscopic morphology of the cross section after CMAS corrosion was observed by scanning electron microscope. Figure 2 The cross-sectional microscopic morphology of the ceramic body after CMAS corrosion is shown in Fig.11 From the comparison of the microscopic morphology of the 3.5DySZ ceramic prepared in Comparative Example 1 after CMAS corrosion, it can be seen that the corrosion zone thickness of 1Sc3.5DySZ is 400μm, which is much smaller than the corrosion thickness of 3.5DySZ ceramic of 1mm, indicating that the CMAS corrosion resistance of 1Sc3.5DySZ ceramic is better than that of 3.5DySZ ceramic.
[0067] Example 2 Preparation of 10 g 2 mol.% Sc2O3-3.5 mol.% Dy2O3-ZrO2
[0068] 0.20855 g of scandium oxide and 0.98710 g of dysprosium oxide were respectively dissolved in hot hydrochloric acid, 23.02550 g of ZrOCl2·8H2O was dissolved in deionized water, 0.5 g of polyethylene glycol (PEG2000) was dissolved in 10 ml of anhydrous ethanol as a dispersant, the above solutions were mixed and fixed to a solution concentration of 0.5 mol / L to obtain a mixed salt solution.
[0069] Measure ammonia water and water in a volume ratio of 1:1 as a precipitant; take 100 ml of deionized water as a reaction mother solution, adjust the pH value of the reaction mother solution to 10 with a precipitant, and simultaneously drop the mixed salt solution and the precipitant into the reaction mother solution for a co-precipitation reaction. Apply magnetic stirring during the precipitation process, and adjust the titration rate of the mixed salt solution and the precipitant to ensure that the pH value of the entire reaction process is constant at 10. After the titration is completed, continue stirring for 30 minutes, let the precipitate stand for 24 hours, and use centrifugal washing to repeatedly wash the precipitate with deionized water for several times until less than Cl is detected by testing with a 1 mol / L AgNO3 solution. - The precipitate was then washed with anhydrous ethanol for three times, and the filter cake obtained after filtering the precipitate was dried at 85°C for 6 hours, and then dried at 110°C for 12 hours to obtain a hydroxide precursor powder.
[0070] The precursor powder was placed in a ball mill and milled for 2 hours at a ball milling rate of 200 r / min. The ball milling medium was anhydrous ethanol. The milled slurry was dried and the obtained dry precursor powder was calcined at 800°C for 2 hours to obtain a 2 mol.% Sc2O3-3.5 mol.% Dy2O3-ZrO2 (2Sc3.5DySZ) composite ceramic powder. The phase composition of the composite powder is as follows: Figure 3 The X-ray diffraction pattern shown shows a single tetragonal phase structure.
[0071] The 2Sc3.5DySZ ceramic powder was passed through a 200-mesh sieve and then pressed at a pressure of 12 MPa and a holding time of 1 min to obtain a particle size of The ceramic compact was subjected to debonding heat treatment at 500°C for 1 h, and then the debonded sample was sintered at 1400°C for 10 h in a box furnace to densify it and obtain a 2Sc3.5DySZ ceramic body.
[0072] According to the method of Example 1, the ceramic body prepared in Example 2 was tested for high temperature phase stability and CMAS corrosion resistance. The test results were as follows: no diffraction peak of the monoclinic phase was found, and the 2Sc3.5DySZ ceramic body still maintained a single tetragonal phase structure. After the 3.5DySZ powder prepared in Comparative Example 1 was heat treated at 1400°C for 110 hours, the tetragonal phase was completely transformed into cubic phase c and monoclinic phase m, indicating that the phase stability of 3Sc3.5DySZ ceramic was significantly improved compared with 3.5DySZ. The CMAS corrosion resistance results showed that the corrosion layer thickness of the 2Sc3.5DySZ ceramic body was less than the corrosion thickness of the 3Sc3.5DySZ ceramic body in Comparative Example 1, indicating that the CMAS corrosion resistance of the 2Sc3.5DySZ ceramic is better than that of the 3.5DySZ ceramic.
[0073] Example 3 Preparation of 10 g 3 mol.% Sc2O3-3.5 mol.% Dy2O3-ZrO2
[0074] 0.31248 g of scandium oxide and 0.98600 g of dysprosium oxide were respectively dissolved in hot hydrochloric acid, 22.75657 g of ZrOCl2·8H2O was dissolved in deionized water, 0.5 g of polyethylene glycol (PEG2000) was dissolved in 10 ml of anhydrous ethanol as a dispersant, the above solutions were mixed and fixed to a solution concentration of 0.5 mol / L to obtain a mixed salt solution.
[0075] Measure ammonia water and water in a volume ratio of 1:1 as a precipitant; take 100 ml of deionized water as a reaction mother solution, adjust the pH value of the reaction mother solution to 10 with a precipitant, and simultaneously drop the mixed salt solution and the precipitant into the reaction mother solution for a co-precipitation reaction. Apply magnetic stirring during the precipitation process, and adjust the titration rate of the mixed salt solution and the precipitant to ensure that the pH value of the entire reaction process is constant at 10. After the titration is completed, continue stirring for 30 minutes, let the precipitate stand for 24 hours, and use centrifugal washing to repeatedly wash the precipitate with deionized water for several times until less than Cl is detected by testing with a 1 mol / L AgNO3 solution. - The precipitate was then washed with anhydrous ethanol for three times, and the filter cake obtained after filtering the precipitate was dried at 85°C for 6 hours, and then dried at 110°C for 12 hours to obtain a hydroxide precursor powder.
[0076] The precursor powder was placed in a ball mill and milled for 2 hours at a ball milling rate of 200 r / min. The ball milling medium was anhydrous ethanol. The milled slurry was dried and the obtained dry precursor powder was calcined at 800°C for 2 hours to obtain a 3 mol.% Sc2O3-3.5 mol.% Dy2O3-ZrO2 (3Sc3.5DySZ) composite ceramic powder. The phase composition of the composite powder is as follows: Figure 4 The X-ray diffraction pattern shown shows a single tetragonal phase structure.
[0077] The 3Sc3.5DySZ ceramic powder was passed through a 200-mesh sieve and then pressed at a pressure of 12 MPa for 1 min to obtain a particle size of The ceramic compact was subjected to debonding heat treatment at 500°C for 1 h, and then the debonded sample was sintered at 1400°C for 10 h in a box furnace to densify it and obtain a 3Sc3.5DySZ ceramic body.
[0078] The high temperature phase stability test of the ceramic body prepared in Example 3 was carried out according to the method of Example 1. The test results are as follows: Figure 5The X-ray diffraction pattern shown in the figure evaluates its phase stability based on the monoclinic phase content. No diffraction peak of the monoclinic phase is found in the figure, and the 3Sc3.5DySZ ceramic body still maintains a single tetragonal phase structure. After the 3.5DySZ powder prepared in Comparative Example 1 is heat treated at 1400°C for 110 hours, the tetragonal phase is completely transformed into cubic phase c and monoclinic phase m, indicating that the phase stability of 3Sc3.5DySZ ceramic is significantly improved compared with 3.5DySZ.
[0079] The CMAS corrosion resistance of the ceramic body prepared in Example 3 was tested according to the method of Example 1. The CMAS corrosion resistance results showed that the corrosion layer thickness of the 3Sc3.5DySZ ceramic body was less than the corrosion thickness of the 3.5DySZ ceramic body in Comparative Example 1, indicating that the CMAS corrosion resistance of the 3Sc3.5DySZ ceramic is better than that of the 3.5DySZ ceramic.
[0080] Example 4 Preparation of 10 g 4 mol.% Sc2O3-3.5 mol.% Dy2O3-ZrO2
[0081] 0.41618 g of scandium oxide and 0.98491 g of dysprosium oxide were respectively dissolved in hot hydrochloric acid, 22.48822 g of ZrOCl2·8H2O was dissolved in deionized water, 0.5 g of polyethylene glycol (PEG2000) was dissolved in 10 ml of anhydrous ethanol as a dispersant, the above solutions were mixed and fixed to a solution concentration of 0.5 mol / L to obtain a mixed salt solution.
[0082] Ammonia water and water in a volume ratio of 1:1 were measured as precipitants; 100 ml of deionized water was taken as the reaction mother solution, the pH value of the reaction mother solution was adjusted to 10 with the precipitant, and the mixed salt solution and the precipitant were simultaneously dripped into the reaction mother solution for co-precipitation reaction. Magnetic stirring was applied during the precipitation process, and the titration rate of the mixed salt solution and the precipitant was adjusted to ensure that the pH value of the entire reaction process was constant at 10. After the titration was completed, stirring was continued for 30 minutes, and the precipitate was allowed to stand for 24 hours. The precipitate was repeatedly washed several times with deionized water by centrifugal washing until less than Cl was detected by testing with 1 mol / L AgNO3 solution. - The precipitate was then washed with anhydrous ethanol for three times, and the filter cake obtained after filtering the precipitate was dried at 85°C for 6 hours, and then dried at 110°C for 12 hours to obtain a hydroxide precursor powder.
[0083] The precursor powder was placed in a ball mill and milled for 2 hours at a ball milling rate of 200 r / min. The ball milling medium was anhydrous ethanol. The milled slurry was dried and the obtained dry precursor powder was calcined at 800°C for 2 hours to obtain a 4 mol.% Sc2O3-3.5 mol.% Dy2O3-ZrO2 (4Sc3.5DySZ) composite ceramic powder. The phase composition of the composite powder is as follows: Figure 6The X-ray diffraction pattern shown shows a single tetragonal phase structure.
[0084] The 4Sc3.5DySZ ceramic powder was passed through a 200-mesh sieve and then pressed at a pressure of 12 MPa and a holding time of 1 min to obtain a particle size of The ceramic compact was subjected to debonding heat treatment at 500°C for 1 h, and then the debonded sample was sintered at 1400°C for 10 h in a box furnace to densify it and obtain a 4Sc3.5DySZ ceramic body.
[0085] The high temperature phase stability test of the ceramic body prepared in Example 4 was carried out according to the method of Example 1. The test results are as follows: Figure 7 The X-ray diffraction pattern shown in the figure evaluates its phase stability based on the monoclinic phase content. No diffraction peak of the monoclinic phase is found in the figure. After heat treatment at 1400°C for 110 hours, the 4Sc3.5DySZ ceramic still maintains a single tetragonal phase structure. After heat treatment at 1400°C for 110 hours, the tetragonal phase t of the 3.5DySZ ceramic prepared in Comparative Example 1 is completely transformed into cubic phase c and monoclinic phase m, indicating that the phase stability of 4Sc3.5DySZ ceramic is significantly improved compared with 3.5DySZ.
[0086] The ceramic body prepared in Example 4 was tested for CMAS corrosion resistance according to the method of Example 1. The test results are as follows: Figure 8 The cross-sectional microscopic morphology of the ceramic body after CMAS corrosion is shown. The structure of the 4Sc3.5DySZ ceramic body is intact, and no obvious layered corrosion area is found, indicating that 4Sc3.5DySZ has excellent CMAS corrosion resistance.
[0087] Example 5 Preparation of 10 g 1 mol.% Sc2O3-3.5 mol.% Dy2O3-ZrO2
[0088] 0.10439 g of scandium oxide and 0.98820 g of dysprosium oxide were respectively dissolved in hot hydrochloric acid, 23.29502 g of ZrOCl2·8H2O was dissolved in deionized water, 0.3 g of polyethylene glycol (PEG2000) was dissolved in 10 ml of anhydrous ethanol as a dispersant, the above solutions were mixed and fixed to a solution concentration of 0.5 mol / L to obtain a mixed salt solution.
[0089] Ammonia water and water in a volume ratio of 1:1 were measured as a precipitant; 100 ml of deionized water was taken as a reaction mother solution, the pH value of the reaction mother solution was adjusted to 11 with a precipitant, and the mixed salt solution and the precipitant were simultaneously dripped into the reaction mother solution for a co-precipitation reaction. Magnetic stirring was applied during the precipitation process, and the titration rate of the mixed salt solution and the precipitant was adjusted to ensure that the pH value of the entire reaction process was constant at 11. After the titration was completed, stirring was continued for 30 minutes, and the precipitate was allowed to stand for 24 hours. The precipitate was repeatedly washed several times with deionized water by centrifugal washing until less than Cl was detected by a 1 mol / L AgNO3 solution. - The precipitate was then washed with anhydrous ethanol for three times, and the filter cake obtained after filtering the precipitate was dried at 85°C for 10 h, and then dried at 120°C for 12 h to obtain a hydroxide precursor powder.
[0090] The precursor powder was placed in a ball mill and milled for 2 hours at a ball milling rate of 200 r / min, and the ball milling medium was anhydrous ethanol. The milled slurry was dried, and the obtained dry precursor powder was calcined at 600°C for 2 hours to obtain 1 mol.% Sc2O3-3.5 mol.% Dy2O3-ZrO2 (1Sc3.5DySZ) composite ceramic powder. The XRD test results of the powder showed that 1Sc3.5DySZ showed a single tetragonal phase structure.
[0091] The 1Sc3.5DySZ ceramic powder was passed through a 200-mesh sieve and then pressed at a pressure of 10 MPa and a holding time of 1 min to obtain a particle size of The ceramic green body was subjected to a debonding heat treatment at 500°C for 1 h, and the ceramic body was subjected to a densification heat treatment at 1400°C for 10 h.
[0092] According to the method of Example 1, the ceramic body prepared in Example 5 was tested for high temperature phase stability and CMAS corrosion resistance. The test results showed that no diffraction peak of the monoclinic phase was found, and the 1Sc3.5DySZ ceramic body still maintained a single tetragonal phase structure. After the 3.5DySZ powder prepared in Comparative Example 1 was heat treated at 1400°C for 110 hours, the tetragonal phase was completely transformed into cubic phase c and monoclinic phase m, indicating that the phase stability of 3Sc3.5DySZ ceramic was significantly improved compared with 3.5DySZ. The CMAS corrosion resistance results showed that the corrosion layer thickness of the 1Sc3.5DySZ ceramic body was less than the corrosion thickness of the 3.5DySZ ceramic body in Comparative Example 1, indicating that the CMAS corrosion resistance of the 1Sc3.5DySZ ceramic prepared in Example 5 was better than that of the 3.5DySZ ceramic.
[0093] Example 6 Preparation of 10 g 1 mol.% Sc2O3-3.5 mol.% Dy2O3-ZrO2
[0094] 0.10439 g of scandium oxide and 0.98820 g of dysprosium oxide were respectively dissolved in hot hydrochloric acid, 23.29502 g of ZrOCl2·8H2O was dissolved in deionized water, 0.4 g of polyethylene glycol (PEG2000) was dissolved in 10 ml of anhydrous ethanol as a dispersant, the above solutions were mixed and fixed to a solution concentration of 0.5 mol / L to obtain a mixed salt solution.
[0095] Ammonia water and water in a volume ratio of 1:1 were measured as a precipitant; 100 ml of deionized water was taken as a reaction mother solution, the pH value of the reaction mother solution was adjusted to 12 with a precipitant, and the mixed salt solution and the precipitant were simultaneously dripped into the reaction mother solution for a co-precipitation reaction. Magnetic stirring was applied during the precipitation process, and the titration rate of the mixed salt solution and the precipitant was adjusted to ensure that the pH value of the entire reaction process was constant at 12. After the titration was completed, stirring was continued for 30 minutes, and the precipitate was allowed to stand for 24 hours. The precipitate was repeatedly washed several times with deionized water by centrifugal washing until less than Cl was detected by a 1 mol / L AgNO3 solution. - The precipitate was then washed twice with anhydrous ethanol, and the filter cake obtained after filtering the precipitate was dried at 85°C for 8 hours, and then dried at 110°C for 15 hours to obtain a hydroxide precursor powder.
[0096] The precursor powder was placed in a ball mill and milled for 2 hours at a ball milling rate of 200 r / min, and the ball milling medium was anhydrous ethanol. The milled slurry was dried, and the obtained dry precursor powder was calcined at 700°C for 2 hours to obtain 1 mol.% Sc2O3-3.5 mol.% Dy2O3-ZrO2 (1Sc3.5DySZ) composite ceramic powder. The XRD test results of the powder showed that 1Sc3.5DySZ showed a single tetragonal phase structure.
[0097] The 1Sc3.5DySZ ceramic powder was passed through a 200-mesh sieve and then pressed at a pressure of 15 MPa and a holding time of 1 min to obtain a particle size of The ceramic green body was subjected to a debonding heat treatment at 500°C for 1 h, and the ceramic body was subjected to a densification heat treatment at 1400°C for 10 h.
[0098] According to the method of Example 1, the ceramic body prepared in Example 6 was tested for high temperature phase stability and CMAS corrosion resistance. No diffraction peak of the monoclinic phase was found in the test results. The 1Sc3.5DySZ ceramic body prepared in Example 6 still maintained a single tetragonal phase structure, while the 3.5DySZ powder prepared in Comparative Example 1 was heat treated at 1400°C for 110 hours, and the tetragonal phase was completely transformed into cubic phase c and monoclinic phase m, indicating that the 1Sc3.5DySZ ceramic prepared in Example 6 has significantly improved phase stability compared with 3.5DySZ. The CMAS corrosion resistance results show that the corrosion layer thickness of the 1Sc3.5DySZ ceramic body is less than the corrosion thickness of the 3.5DySZ ceramic body in Comparative Example 1, indicating that the CMAS corrosion resistance of the 1Sc3.5DySZ ceramic prepared in Example 6 is better than that of the 3.5DySZ ceramic.
[0099] Comparative Example 1 Preparation of 10 g 3.5 mol.% Dy2O3-ZrO2
[0100] 0.98930 g of dysprosium oxide was weighed and dissolved in hot hydrochloric acid, 23.56515 g of ZrOCl2·8H2O was weighed and dissolved in deionized water, 0.5 g of polyethylene glycol (PEG2000) was weighed and dissolved in 10 ml of anhydrous ethanol as a dispersant, and the above solutions were mixed and fixed to a solution concentration of 0.5 mol / L to obtain a mixed salt solution.
[0101] Measure ammonia water and water in a volume ratio of 1:1 as a precipitant; take 100 ml of deionized water as a reaction mother solution, adjust the pH value of the reaction mother solution to 10 with a precipitant, and simultaneously drop the mixed salt solution and the precipitant into the reaction mother solution for a co-precipitation reaction. Apply magnetic stirring during the precipitation process, and adjust the titration rate of the mixed salt solution and the precipitant to ensure that the pH value of the entire reaction process is constant at 10. After the titration is completed, continue stirring for 30 minutes, let the precipitate stand for 24 hours, and use centrifugal washing to repeatedly wash the precipitate with deionized water for several times until less than Cl is detected by testing with a 1 mol / L AgNO3 solution. - The precipitate was then washed with anhydrous ethanol for three times, and the filter cake obtained after filtering the precipitate was dried at 85°C for 6 hours, and then dried at 110°C for 12 hours to obtain a hydroxide precursor powder.
[0102] The precursor powder was placed in a ball mill and milled for 2 hours at a ball milling rate of 200 r / min. The ball milling medium was anhydrous ethanol. The milled slurry was dried and the obtained dry precursor powder was calcined at 800°C for 2 hours to obtain a 3.5 mol.% Dy2O3-ZrO2 (3.5DySZ) composite ceramic powder. The phase composition of the composite powder is as follows: Fig. 9 The X-ray diffraction pattern shown shows a single tetragonal phase structure.
[0103] The 3.5DySZ ceramic powder was passed through a 200-mesh sieve and then pressed at a pressure of 12 MPa for 1 min to obtain a particle size of The ceramic compact was subjected to debonding heat treatment at 500°C for 1 h, and then the debonded sample was sintered at 1400°C for 10 h in a box furnace to densify it and obtain a 3.5DySZ ceramic body.
[0104] The high temperature phase stability test of the ceramic body prepared in Comparative Example 1 was carried out according to the method of Example 1. The test results are as follows: Fig.10 The X-ray diffraction pattern shown in the figure evaluates the phase stability based on the monoclinic phase content. After the 3.5DySZ ceramic is heat treated at 1400℃ for 110h, the tetragonal phase is completely transformed into the cubic phase and the monoclinic phase.
[0105] The ceramic body prepared in Comparative Example 1 was tested for CMAS corrosion resistance according to the method of Example 1. The test results are as follows: Fig.11 As shown, the microscopic morphology of the cross section of the ceramic body after CMAS corrosion shows that the corrosion area of 3.5DySZ ceramics is peeled off and the corrosion depth reaches 1mm.
[0106] Through Examples 1 to 4, by controlling a single variable (the molar percentage of Sc2O3), the high-temperature phase stability and corrosion resistance of the zirconia-based ceramic material with a high Sc2O3 doping amount are more excellent.
[0107] In view of the high-temperature phase change problem of YSZ in the prior art and the problem that a single Dy2O3-doped stable zirconia system is susceptible to CMAS corrosion, the present invention designs and develops a binary rare earth oxide composite-doped stable zirconia system. Through component design and regulation, a zirconia-based ceramic material with high phase stability and excellent resistance to CMAS corrosion is obtained, which can be used for the surface ceramic layer material of thermal barrier coatings.
[0108] Although the present invention has been described and illustrated with reference to specific embodiments of the present invention, these descriptions and illustrations do not limit the present invention. It will be clearly understood by those skilled in the art that various changes may be made without departing from the true spirit and scope of the present invention as defined by the appended claims, so that specific circumstances, materials, material compositions, materials, methods or processes are suitable for the goals, spirit and scope of the present application. All such modifications are intended to be within the scope of the appended claims. Although the methods disclosed herein have been described with reference to specific operations performed in a specific order, it should be understood that these operations may be combined, subdivided or reordered to form equivalent methods without departing from the teachings of the present invention. Therefore, unless specifically indicated herein, the order and grouping of operations are not limitations of the present application.
Claims
1. A zirconia-based ceramic material with high phase stability and resistance to CMAS corrosion, characterized in that: The zirconia-based ceramic material is a binary rare earth oxide co-doped stable zirconia material, wherein the binary rare earth oxide comprises dysprosium oxide and scandium oxide; The doping amount of the binary rare earth oxide in the zirconium oxide-based ceramic material is 4-8 mol; The molar ratio of scandium oxide to dysprosium oxide is 1:(6-1).
2. A method for preparing the zirconia-based ceramic material with high phase stability and resistance to CMAS corrosion according to claim 1, comprising: The composite ceramic powder is pressed and sintered to obtain a zirconia-based ceramic material with high phase stability and resistance to CMAS corrosion; The composite ceramic powder comprises: Sc2O3, Dy2O3 and ZrO2.
3. The preparation method according to claim 2, characterized in that: The preparation method of the composite ceramic powder comprises: The hydroxide precursor is dried and calcined to obtain composite ceramic powder.
4. The preparation method according to claim 3, characterized in that: The preparation method of the hydroxide precursor comprises: The mixed cation solution is subjected to a coprecipitation reaction in a reaction mother solution to obtain a hydroxide precursor; The mixed cationic solution comprises: solution A and solution B; The solute in the solution A includes scandium oxide and dysprosium oxide; the solvent in the solution A includes hydrochloric acid; The solution B is selected from zirconium oxychloride solution; The reaction mother liquor is selected from water, and the pH value of the reaction mother liquor is adjusted by ammonia water. The pH value of the reaction mother liquor is 9-13.
5. The preparation method according to claim 4, characterized in that: Ammonia water is used to adjust the pH value of the reaction during the coprecipitation reaction; The mixed cationic solution further comprises: a dispersant; After the coprecipitation reaction, the mixture is allowed to stand.
6. The preparation method according to claim 5, characterized in that: After the standing, the following steps are also included: The obtained product is filtered and washed; The washing method comprises: Wash first with water and then with ethanol.
7. The preparation method according to claim 2, characterized in that: The pressing pressure is selected from 10 to 30 MPa; The sintering temperature is 1300-1600°C.
8. A thermal barrier coating comprising: The zirconia-based ceramic material with high phase stability and resistance to CMAS corrosion as described in claim 1.
9. An environmental barrier coating comprising: The zirconia-based ceramic material with high phase stability and resistance to CMAS corrosion as described in claim 1.